If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7a = 6a + -6 Reorder the terms: 7a = -6 + 6a Solving 7a = -6 + 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. 7a + -6a = -6 + 6a + -6a Combine like terms: 7a + -6a = 1a 1a = -6 + 6a + -6a Combine like terms: 6a + -6a = 0 1a = -6 + 0 1a = -6 Divide each side by '1'. a = -6 Simplifying a = -6
| 25000=2x+5 | | 1=3(b+8)-(-1+6b) | | 178=5x+x | | 40-3x=10+12x | | 8x-5+2x=0 | | 4(a+2)+5=23 | | 7x^2-141x-30=0 | | 0.25r-0.25+0.15r=0.5-0.25r | | 3x+4x-x=14+30-2 | | -7x+1=3+10x | | 160t^2=480t-360 | | 24.4-10.4=p | | 3n+4-2n+6= | | 10.4-24.4=p | | 3x^2-7x-1.2=0 | | 42+4x=62-1x | | 4x+7y-7z=-10 | | -4-7x=66 | | OnehalfX+16=39 | | x^2+4x-5y^2+20y-20=0 | | -17x-14=-150 | | 137=28x*428+37 | | (7-3i)(-2-5i)=0 | | 9y+3-y=12y | | 9r+1-7r+1=-15 | | -28x+32x=-30 | | 0.12-0.02(x+3)=-0.03(3-x) | | .33w=2.5 | | -3.6=2f | | 10(t-3)+4t=7(2t+2)-9 | | 19(4.5-.25x)+x=13 | | -32=-4(v+9) |